La cuestión de la limpieza de sangre y la disimulación religiosa en algunos entremeses del siglo xvii : de la burla a la sátira social - Carine Herzig (Les Cahiers de Framespa)
From the beginning of the 17th century, the entremés became increasingly popular to the point of becoming one of the highlights of the theatrical show. The authors make fun of the society of their time and of some of these most remarkable "types" (such as the mayor or the local judge, for example), by resorting to ridicule and exaggeration. Beyond their purely comic character, many of these plays offer a satire of concrete aspects of social and political life, particularly those related to blood purity and the condition of the old Christian. The purpose of this work is to show how, in some of their companies, Cervantes and Benavente openly criticize prejudices related to these concepts, through gender-specific processes.